Trading Costs on the Stock Exchange of Thailand - JENWITTAYAROJE, Nattawut (Institutional Knowledge at Singapore Management University, 2015)
This study examines the components of trading costs incurred in trading large and liquid stocks listed on the Stock Exchange of Thailand. We find that aggressive orders pay an immediacy price measured by price impact, whereas executed passive orders gain the immediacy price. We also find a sizable opportunity cost from the unexecuted portion of a limit order that more than offsets the benefit obtained from the partial fulfillment of the order. The total trading cost, which includes price impact and opportunity cost, is positively related to order size and stock price volatility, but negatively associated with firm size, stock price, and stock liquidity. The total trading cost has a U-shaped relation with order aggressiveness. Collectively, our study suggests that, to minimize the total trading cost, the optimal strategy is simply to use a limit order submitted at the best quote.